The Role of Islamic Religious Education on Behavior and Competition in the World of Work - nela melani; pipit nurhayati; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
Abstract - Islamic education today is faced with the challenges of modern human life that are filled with various problems that are quite complex; among others is "how Islamic education can be of high quality with the ability to foster good morals in the face of societal changes that take place so quickly that Islamic education products can serve the needs of the afterlife, but also must be able to compete competitively and proactively in the modern world of society". In life and work, it teaches the importance of future orientation. It grows with a consequential attitude in the form of behavior that always leads to an efficient (energy-efficient) way of working. This attitude became the basis for "the effort to make human beings who have always been so oriented towards productive values. Work casually, have no plan, lazy, wasteful energy, time, and cost is precisely the opposite to Islamic values" Islam teaches that every second of time must be filled with three things: "increased faith, pious charity, and social communication".